PENGARUH KEBUTUHAN AKAN PRESTASI, EFIKASI DIRI, KESIAPAN INSTRUMENTASI, DAN FAKTOR DEMOGRAFIS PADA INTENSI KEWIRAUSAHAAN MAHASISWA PEMENANG PROGRAM MAHASISWA WIRAUSAHA - Ignatius Soni Kurniawan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
This research adopted Indarti dan Rostiani (2008) research framework. It aimed to examine influencing need for achievement, self eficacy, instrumental readiness and demographics variable (gender, educational background, job experience) partially to entrepreneural intention. The sample of the reserach was university student the winner of Program Mahasiswa Wirausaha located in Kopertis 7 Surabaya. The sample was taken applying a non-probability method with a purposive sampling technique. The data collecting was carried out using direct survey technique with questionnaires. The data were analyzed by multiple regression statistic. The result of the analysis reveals that self eficacy, gender, and educational background partially influencing entrepreuneural intention. Whereas need for achievement, instrumental readiness and job experience not influencing entrepreneural intention. Keywords: need for achievement, self eficacy, instrumental readiness, gender, educational background, job experience, intrepreneural intention